Improvement of Solution Problems of Matrix Equations Calculated by Computers - Levent CIVCIK; Cevdet ÇETIN; Haydar BULGAK (International Journal of Applied Methods in Electronics and Computers, 2015)
Solution of linear algebra systems may come out with “ill-condition” or “well-condition” based on input information and solution methods. The aim of this study is to determine and correction of problems that may come out from the solution of matrix equations by computers and to calculate linear algebra.